2022
DOI: 10.1039/d2re00041e
|View full text |Cite
|
Sign up to set email alerts
|

Copper/TEMPO-catalyzed continuous aerobic alcohol oxidation in a micro-packed bed reactor

Abstract: A micro-packed bed reactor has been developed to demonstrate aerobic oxidation of alcohols to aldehydes, utilizing green oxidant O2 and effective Cu/TEMPO-catalyzed system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…[12][13][14] In general, MPB is installed with small catalyst particles (diameter <500 μm) to manufacture microchannels and cavities. [15][16][17] However, the pressure drop is increased in the MPB with catalyst particles of such small size, resulting in high energy consumption. 18 Metal foam can be used for fabricating monolithic catalysts in the MPB with the advantages of large accessible porosity, high mechanical strength, and low pressure drop.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] In general, MPB is installed with small catalyst particles (diameter <500 μm) to manufacture microchannels and cavities. [15][16][17] However, the pressure drop is increased in the MPB with catalyst particles of such small size, resulting in high energy consumption. 18 Metal foam can be used for fabricating monolithic catalysts in the MPB with the advantages of large accessible porosity, high mechanical strength, and low pressure drop.…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29] The intrinsic kinetics of the reaction can be determined quickly and accurately based on μPBRs. [30][31][32] In this work, the efficient and continuous conversion of FUR to FA in μPBRs was investigated based on the methods of molecular hydrogenation and catalytic transfer hydrogenation. Firstly, the performances of Cu-, Ni-, Pd-and Pt-based catalysts for FUR hydrogenation were screened at different temperatures to obtain suitable catalysts in μPBRs.…”
Section: Introductionmentioning
confidence: 99%
“…27–29 The intrinsic kinetics of the reaction can be determined quickly and accurately based on μPBRs. 30–32…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the superiority of micropacked bed reactors (μPBRs) for mass transfer enhancement has received much attention due to the small particle size ( d p < 500 μm) and reactor volume. Typical mass transfer results of μPBRs showed that gas–liquid volumetric mass transfer coefficients and external volumetric mass transfer coefficients were 0.12–0.39 and 0.15–2.76 s –1 , respectively, which were higher than those of STRs and TBRs. , Also, μPBRs have several advantages of fast heat removal, catalyst immobilization, plug flows, and improved safety. Owing to these features, μPBRs have been used in gas–liquid–solid and gas–liquid reactions, such as hydrogenations, oxidations, , absorption of CO 2 , and wastewater treatments by ozonolysis. , The reduced dimension of reactors and particles can shift the dominant force of the fluid from the gravity to capillary force, resulting in a high pressure drop and energy consumption of μPBRs.…”
Section: Introductionmentioning
confidence: 99%